Influence of Covid-19 Pandemic Climate, Discipline, Motivation to Performance in BAERT Kupang City - Riwukore, Jefirstson Richset; Yustini, Tien; Zamzam, Fakhry; Habaora, Fellyanus (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2022)
This research aimed to analyze the influence of the Covid-19 pandemic climate, work discipline, and work motivation on the performance of the state civil apparatus. This research was implemented from January to June 2021 at the Body of Apparatus, Education, and Training of Kupang City. The research method in this article uses a quantitative approach. The population and sample in this study were 123 ASN in the Body of Apparatus, Education, and Training of Kupang City. At the same time, the data analysis technique used multiple linear regression analysis. This study indicates that the Covid-19 pandemic climate and work discipline have no effect on employee performance, but work motivation positively influences employee performance. Simultaneously, the Covid-19 pandemic climate variables, work discipline, and work motivation positively and significantly influence employee performance.